Effect of polyherbal supplementation on milk production and postpartum reproduction in crossbred cattle - Bipate, Mahesh; Misra, Arun Kumar (Indian Journal of Dairy Science, 2020)
The present study was conducted at farmerâ€™s field in Muzaffarnagar district of Uttar Pradesh to assess the response of polyherbal mixture supplementation on milk production and postpartum reproduction in crossbred cattle. The polyherbal mixture was prepared by mixing 25 g each ofÂ Foeniculum vulgare (Saunf), Trachy spermumammi (Ajwain), Trigonella foenum-graecum (Methi), Zingiber officinale (Sundh), Anethum graveolens (Sowa) and Elettaria cardamomum (Cardamom).Â Sixteen crossbred cattle were divided into two groups on eight each as T0: control and T1: treatment and the animals of T1 were supplemented ployherbal mixture from the day of calving till day 10 of postpartum. The data was recorded for 2 months duration. The animals were managed as per the standard feeding practices followed by the farmers. Significant increase in milk yield (P<0.05) was recorded due to supplementation of polyherbal mixture as compared to control group. An average increase of 21.53 % in milk yield was recorded due to polyherbal mixture supplemention as compared to 6.91% in unsupplemented group. No case of foetal membrane retention was recorded in treatment group, whereas in control group, two cases were observed. Time required for expulsion of foetal membranes was reduced significantly (P<0.05) in supplemented animal as compared to control (4.38 vs 7.38 hours). Supplementation has also reduced number of insemination per conception in cattle (2.38) as compared un-supplemented group (2.88). Considering the present cost of feed supplement and the market price of milk, polyherbal mixture supplementation appears to be both economical and cost effective, and had a positive effect on milk production and postpartum reproduction in crossbred cattle maintained under small holder conditions.